The Effectiveness of Teaching Materials of Local-Wisdom Based Picture Storybooks on the Eco-Literacy of Elementary School Students - Devi Afriyuni Yonanda; Nana Supriatna; Kama Abdul Hakam; Wahyu Sopandi (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThe underlying background of this research with the importance of eco-literacy for students' elementary school. Ecoliteracy refers to the awareness of protecting nature and consuming local food for a healthy life. This experimental research aims to described the effectiveness of local wisdom-based picture storybook teaching materials on the eco-literacy of elementary school students. The applied design was a pretest-posttest control group design with a random sampling technique. The researchers used theme 3, caring for livings, and subtheme three, about loving the environment for the fourth graders of 2 (two) elementary schools in Indramayu, West Java. The results were 1) no significant experience increase found in the control group and 2) a significant experience increase found in the experimental group. Both groups' obtained N-gain values had huge differences, indicating the effectiveness of the applied local-wisdom-based picture storybook to improve studentsâ€™ eco-literacy.Keywords: teaching materials, local wisdom, eco-literacy.AbstrakÂ Penelitian ini dilatarbelakangi oleh pentingnya eco-literacy bagi siswa sekolah dasar. Ekoliterasi mengacu pada kesadaran menjaga alam dan mengkonsumsi pangan lokal untuk hidup sehat. Penelitian eksperimen ini bertujuan untuk mendeskripsikan keefektifan bahan ajar buku cerita bergambar berbasis kearifan lokal terhadap literasi lingkungan siswa sekolah dasar. Desain yang digunakan adalah pretest-posttest control group design dengan teknik random sampling. Peneliti menggunakan tema 3, merawat kehidupan, dan subtema tiga, tentang mencintai lingkungan untuk siswa kelas IV dari 2 (dua) sekolah dasar di Indramayu, Jawa Barat. Hasilnya adalah 1) tidak ada peningkatan pengalaman yang signifikan pada kelompok kontrol dan 2) peningkatan pengalaman yang signifikan pada kelompok eksperimen. Nilai N-gain yang diperoleh kedua kelompok memiliki perbedaan yang sangat besar, hal ini menunjukkan keefektifan penerapan buku cerita bergambar berbasis kearifan lokal untuk meningkatkan eco-literacy siswa.Kata kunci: bahan ajar, kearifan lokal, eko-literasi.